KOMUNIKASI KEBIJAKAN PENCEGAHAN DAN PENANGANAN KEKERASAN DI LINGKUNGAN UNIVERSITAS DIPONEGORO : STUDI PADA SATGAS PPK-PT UNIVERSITAS DIPONEGORO - Aretha Sandrina; Amni Zarkasyi Rahman (Journal of Management and Public Policy, 2026)
Policy communication is a vital aspect of policy implementation, particularly in ensuring that policy-related information is effectively transmitted, received, and understood by both implementers and the policy’s target. In the context of preventing and handling violence in education aspect, policy communication plays a central role in disseminating information regarding the existence, roles, and operational mechanisms of the Task Force for the Prevention and Handling of Violence in Higher Education (Satgas PPK PT) to the academic community. This study aims to analyze how policy communication is implemented in the execution of such policies at Diponegoro University using a qualitative approach, with data collected through in-depth interviews to capture the perspectives and experiences of relevant informants. The analysis is guided by George Edward III’s policy implementation framework, which emphasizes three factors of communication, which are transmission, clarity, and consistency. The results reveal that policy communication conducted by the Satgas PPK-PT at Diponegoro University has not been fully optimal, particularly due to limited dissemination reach and the low visibility of messages among students, resulting in uneven levels of awareness regarding the task force’s functions and procedures. Consequently, there is a need to strengthen communication strategies by enhancing the reach, clarity, and consistency of information delivery so that policy messages can be more effectively and evenly understood across the academic community, thereby supporting the overall success of violence prevention and handling policies in higher education